Formation and prevention of fractures in sol–gel-derived thin films. Issue 5 (3rd December 2014) - Kappert, Emiel J.; Pavlenko, Denys; Malzbender, Jürgen; Nijmeijer, Arian; Benes, Nieck E.; Tsai, Peichun Amy
Abstract : Sol–gel-derived thin films play an important role as the functional coatings for various applications that require crack-free films to fully function. Abstract : Sol–gel-derived thin films play an important role as the functional coatings for various applications that require crack-free films to fully function. However, the fast drying process of a standard sol–gel coating often induces mechanical stresses, which may fracture the thin films. An experimental study on the crack formation in sol–gel-derived silica and organosilica ultrathin (submicron) films is presented. The relationships among the crack density, inter-crack spacing, and film thickness were investigated by combining direct micrograph analysis with spectroscopic ellipsometry. It is found that silica thin films are more prone to fracturing than organosilica films and have a critical film thickness of 300 nm, above which the film fractures. In contrast, the organosilica films can be formed without cracks in the experimentally explored regime of film thickness up to at least 1250 nm. These results confirm that ultrathin organosilica coatings are a robust silica substitute for a wide range of applications.